Investigation of the Relation between South and Southwest Iran\'s Heavy Rainfall with Atmospheric Rivers (ARs). - Nesa sepandar; kamal omidvar (تحقیقات کاربردی علوم جغرافیایی)
In this study, we tried to identify the sources of moisture and its direction of heavy rainfall in south and southwest of Iran by using a new algorithm based on atmospheric rivers. For this purpose, daily rainfall of 17 synoptic stations in the period 1986 to 2015 in south and southwestern Iran that have a common time span and fully cover the study area is used.Also from the data set of the National Center for Environmental Prediction / National Center for Atmospheric Research (NCEP / NCAR) European Mid-Term Forecast Center (ECMWF) and ERA-interim data with spatial resolution of 0.75 It was used at 0.75 latitude and longitude with 6 hour resolution. The variables used are integrated water vapor (IWV), specific humidity (q), and orbital and meridional components (u, v). In this research, an algorithm based on the calculation of Vertical Horizontal Vapor Transfer Integral (IVT) is used to identify and navigate atmospheric rivers. The results show that the main source of rainfall moisture is in south and southwestern Iran, south of Red Sea and Gulf of Aden. Of course, the maps show that the Arabian Sea was not affected by the humidity.The Arabian Peninsula also, due to the high moisture transfer rate, as a transitional route, transmits a large amount of moisture to the study area.Finally, the path of moisture to the study area was mapped and identified, and thus considering the three main conditions for the atmospheric river, it can be said that the path obtained is the same as the atmospheric river.